Methods for Comparison of Potentialities of Fishing Grounds and Efficiencies of Gears - Venkateswara Rao, K. (Fishery Technology, 2025)
The potentialities of fishing grounds were studied using the non-parametric methods; Wilcoxon test, Sign test, Run test and Median test and the two fishing grounds tested were found equipotential. Gear efficiency was also studied by non-parametric methods.